2021
DOI: 10.1109/tnsre.2021.3082056
|View full text |Cite
|
Sign up to set email alerts
|

Sharpened and Mechanically Durable Carbon Fiber Electrode Arrays for Neural Recording

Abstract: Bioelectric medicine treatments target disorders of the nervous system unresponsive to pharmacological methods. While current stimulation paradigms effectively treat many disorders, the underlying mechanisms are relatively unknown, and current neuroscience recording electrodes are often limited in their specificity to gross averages across many neurons or axons. Here, we develop a novel, durable carbon fiber electrode array adaptable to many neural structures for precise neural recording. Carbon fibers (6.8 µm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 66 publications
(90 reference statements)
0
33
0
Order By: Relevance
“…The development of small microelectrodes for localized neural stimulation is the key challenge facing neural interfaces. CFEA have proven to effectively provide neural recording from the motor cortex (Patel et al, 2015(Patel et al, , 2016Massey et al, 2019) as well as from the peripheral nerve (Gillis et al, 2018;Dehdashtian et al, 2020;Welle et al, 2021). We recently (Della Valle et al, 2021) demonstrated how electroplated PtIr can decrease CF impedance with a good coating adherence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The development of small microelectrodes for localized neural stimulation is the key challenge facing neural interfaces. CFEA have proven to effectively provide neural recording from the motor cortex (Patel et al, 2015(Patel et al, , 2016Massey et al, 2019) as well as from the peripheral nerve (Gillis et al, 2018;Dehdashtian et al, 2020;Welle et al, 2021). We recently (Della Valle et al, 2021) demonstrated how electroplated PtIr can decrease CF impedance with a good coating adherence.…”
Section: Discussionmentioning
confidence: 99%
“…The carbon fiber electrode arrays (CFEA) consist of eight sharpened CFs coated with a Parylene C insulation layer (800 nm) and are attached to a small printed circuit board [ZIF Probe, ZIF, (Patel et al, 2016)]. Insulation is removed at the tip using a blowtorching process (Welle et al, 2021) to expose 100-150 μm of carbon with sharpened tips. The final tip diameter tapers from 8.4 to ∼2 μm diameter at the tip.…”
Section: Carbon Fibers Microelectrode Arrays Fabricationmentioning
confidence: 99%
See 1 more Smart Citation
“…[104] Carbon fibers are typically thinner, more flexible, and as biocompatible as thin metal films [105] and are particularly compatible with processing of thin polymeric films. [106] The fibers can be commercially purchased, even preinsulated at micrometer-scale diameters, and arranged in various geometries to fabricate electrical tracks [107][108][109][110][111] or can form a "carbon fabric" that can be cut to form the electrical tracks. [77] Carbon macroparticles, such as carbon black, can be mixed with a polymeric matrix and screen printed, extruded, or 3D-printed for further control over the formulation and pattering.…”
Section: Graphene and Other Carbon Materialsmentioning
confidence: 99%
“…[4,5] The development of intrafascicular devices enabled researchers to detect and modulate neural activities at a higher resolution. To date, a variety of intrafascicular recording and/or stimulation methods have been achieved using thin-film polymer devices, [6,7] carbon fiber electrode arrays, [8,9] highly conductive carbon-based threads with low electrochemical impedance, [10][11][12] Utah arrays, [13,14] flexible microneedle electrode arrays, [15][16][17] and regenerative devices. [18] With implantation of such devices, researchers were able to map and decode Peripheral nerve mapping tools with higher spatial resolution are needed to advance systems neuroscience, and potentially provide a closed-loop biomarker in neuromodulation applications.…”
Section: Introductionmentioning
confidence: 99%